A study and analysis of digital image processing and recognition algorithms. (2014) - Ma, Bin; Bian, Shuhai; Huang, Kuan; Wang, Changtao; Han, Zhonghua; Lin, Song
In this paper, we study and analyse the recognition methods for digital image. In the digital image preprocessing, the conservative smoothing, mean filtering, Gaussian sharpening and binarisation are used together so as to guarantee the effectiveness of the digital feature extraction. We propose an edge-tracking method, a distance feature information method and a feature information extraction method for recognising digital images. And, those three methods are evaluated and compared by experimental tests.